Surveillance of adverse effects of sanitizers among hospital workers: an experience report - Laiane Mucio Correia; Ana Paula dos Santos Campos; Beatriz Ferreira Martins; Madga Lúcia Felix de Oliveira (Universidade de Fortaleza, 2014)
Objective: To report the epidemiological surveillance of intoxication from sanitizers using the method of active case finding of hospital workers who experienced adverse effects. Data Synthesis: Experience report of university extension activities developed at the Center for Intoxication Control of the Regional University Hospital of Maringá in the period from 2010 to 2011. The activities focused on the application of the Surveillance-Education-Assistance triad. In all, 25 hospital workers who experienced adverse effects of sanitizers participated in the study. Data collection occurred through documentary research, analysis of monthly reports, and Notification Forms for Adverse Effects. After that, a semistructured interview was conducted with the subjects. Data were compared with the literature, and the results were presented in three moments: description of the active case finding process; exposure of the settings and implementation of the experience, and conclusive analysis of the experience. The main complaints of the interviewees were nasal congestion, burning eyes, sore throat and headache. All the workers reported using Personal Protective Equipment (PPE). However, eight interviewees were referred to the occupational medical service and received guidance on the use of specific PPE. Five of them confirmed following the guidelines and all remained in the same job. Conclusion: The epidemiological and sanitary surveillance of adverse effects of sanitizers among workers and patients of the University Hospital of Maringá hasthe function to identify, analyze and prevent the adverse effects of sanitizers at the hospital and investigate the notifications doi:10.5020/18061230.2013.p442